Corruption and Human Rights in the Dimension of Pancasila Values - Falah, Muchamad Fajrul (Indonesian Journal of Pancasila and Global Constitutionalism, 2023)
Pancasila is the source of all laws in Indonesia, all regulations made in Indonesia are all based on the values contained in Pancasila. Corruption is a criminal act committed by a person or group of people by taking rights that should belong to the state or society for personal purposes. Corruption is also one of the factors that hinders the economy of a country, can also reduce the country's economy and increase the level of poverty. The act of corruption is an act of serious human rights violation, because it deliberately seizes the property rights of others. This criminal act of corruption usually occurs because of the abuse of power, trust, authority, and the weakness of the law in this country.